Viva São João! Um paralelo luso-brasileiro dos circuitos juninos (Braga x Fortaleza) e seus processos folkmidiáticos audiovisuais. - Carvalho, Bruna Franco Castelo Branco (2024)
The present thesis purposes to investigate how the São João festival cycles are currently organized in the Portuguese city of Braga and the Brazilian city of Fortaleza (CE), drawing a comparative Portuguese-Brazilian parallel between both from the cultural and struc-tural point of view of the festivities of june, since the two cities attract attention from media interests (Freitas, 2011) and tourists (Castro, 2012) on the events of the month of June. The objective of the thesis aims to identify the comparative features between the structures, cultural expressions and arrangement of contemporary Brazilian and Portu-guese June festivities; as well as verifying the audiovisual folk communication processes promoted by the television channels TV Verdes Mares and Braga TV in their respective countries of operation. On a qualitative ethnographic methodological nature, the re-search is based on a comparative case study (Meirinhos, Osório; 2010), applying different techniques for data collection, such as: participant observation, semi-structured inter-views (Sampieri, 2014), bibliographic research and document analysis (Zanella, 2013). Supported by the theory of folkcommunication (Beltrão, 2014), we analyzed separately the 2023 edition of “Arraiá do Ceará” and “São João de Braga”, also identifying the folkmedia process (Luyten, 2002) of elaboration and presentation of June thematic cam-paigns from TV Verdes Mares, in Brazil, and Braga TV, in Portugal. As an investigative result, we found that the content offered by the two communication vehicles is signifi-cant for the process of distinguishing cities (Lefèbvre, 2001) in their respective countries, as they testify to the complex diversity that exists in the feast of Saint John as a multiple and heterogeneous phenomenon, which is particularized by nature, festive pattern and historical process constructed by each society.